SILICA AND PYROXENE IN IVA IRONS; POSSIBLE FORMATION OF THE IVA MAGMA BY IMPACT MELTING AND REDUCTION OF L-LL-CHONDRITE MATERIALS FOLLOWED BY CRYSTALLIZATION AND COOLING - Wasson J.T.; Matsunami Y.; Rubin A.E. (My University, 2006)
Group IVA is a large magmatic group of iron meteorites. The mean ?17O (=?17O - 0.52??18O) of the silicates is ?+1.2?, similar to the highest values in L chondrites and the lowest values in LL chondrites; ?18O values are also in the L/LL range. This strongly suggests that IVA irons formed by melting L-LL parental material, but the mean Ni content of IVA irons (83 mg/g) is much lower than that of a presumed L-LL parent (?170 mg/g) and the low-Ca pyroxene present in two IVA meteorites is Fs13, much lower than the Fs20-29 values in L and LL chondrites. Thus, formation from L-LL precursors requires extensive addition of metallic Fe, probably produced by reduction of FeS and FeO. Group IVA also has S/Ni, Ga/Ni, and Ge/Ni ratios that are much lower than those in L-LL chondrites or any chondrite group that preserves nebular compositions, implying loss of these volatile elements during asteroidal processing. We suggest that these reduction and loss processes occurred near the surface of the asteroid during impact heating, and resulted partly from reduction by C, and partly from the thermal dissociation of FeS and FeO with loss of O and S. The hot (?1770 K) low-viscosity melt quickly moved through channels in the porous asteroid to form a core. Two members of the IVA group, S?o Jo?o Nepomuceno (hereafter, SJN) and Steinbach, contain moderate amounts of orthopyroxene and silica, and minor amounts of low-Ca clinopyroxene. Even though SJN formed after ?26% crystallization and Steinbach formed after ?77% crystallization of the IVA core, both could have originated within several tens of meters of the core-mantle interface if 99% of the crystallization occurred from the center outwards. Two other members of the group (Gibeon and Bishop Canyon) contain tabular tridymite, which we infer to have initially formed as veins deposited from a cooling SiO-rich vapor. The silicates were clearly introduced into IVA irons after the initial magma crystallized. Because the ?-iron crystals in SJN are typically about 5 cm across, an order of magnitude smaller than in IVA irons that do not contain massive silicates, we infer that the metal was in the ?-iron field when the silicates were injected. The SJN and Steinbach silicate compositions are near the low-Ca-pyroxene/silica eutectic compositions. We suggest that a tectonic event produced a eutectic-like liquid and injected it together with unmelted pyroxene grains into fissures in the solid metal core. Published estimates of IVA metallographic cooling rates range from 20 to 3000 K/Ma, leading to a hypothesized breakup of the core during a major impact followed by scrambling of the core and mantle debris [Haack, H., Scott, E.R.D., Love, S.G., Brearley, A. 1996. Thermal histories of IVA stony-iron and iron meteorites: evidence for asteroid fragmentation and reaccretion. Geochim. Cosmochim. Acta 60, 3103-3113]. This scrambling model is physically implausible and cannot explain the strong correlation of estimated cooling rates with metal composition. Previous workers concluded that the low-Ca clinopyroxene in SJN and Steinbach formed from protopyroxene by quenching at a cooling rate of 1012 K/Ma, and suggested that this also supported an impact-scrambling model. This implausible spike in cooling rate by a factor of 1010 can be avoided if the low-Ca clinopyroxene were formed by a late shock event that converted orthopyroxene to clinopyroxene followed by minimal growth in the clinopyroxene field, probably because melt was also produced. We suggest that metallographic cooling-rate estimates (e.g., based on island taenite) giving similar values throughout the metal compositional range are more plausible, and that the IVA parent asteroid can be modeled by monotonic cooling followed by a high-temperature impact event that introduced silicates into the metal and a low-temperature impact event that partially converted orthopyroxene into low-Ca clinopyroxene. ? 2006 Elsevier Inc. All rights reserved.
Keywords: CHONDRITE; IRON METEORITE; MAGMA; MELTING; PYROXENE; SILICA